Paul's Place in the Story: N. T. Wright's Vision of Paul - Schreiner, Thomas R. (Journal for the study of Paul and his letters, 2014)
This article first summarizes Wright's contribution, including the historical context of Paul's day, Paul's world view (focusing on symbol and praxis), his theology (centering on monotheism, election, and eschatology), and the application of Paul's theology to his context. An evaluation of Wright's contribution follows, in which both the strengths and weaknesses of this massive work are set forth. Wright's overarching synthesis of Paul's thought in the culture of his day stands out, but questions are also raised on a few issues, particularly Wright's construal of justification.